Takotsubo cardiomyopathy in a patient with an ascending colon mass - Juan J. Gonzalez; Ahsan Wahab; Mohamed Elgamal; Kavitha Kesari (Journal of Community Hospital Internal Medicine Perspectives, 2018)
Takotsubo cardiomyopathy (TTC) is a syndrome characterized by transient regional systolic dysfunction of the left ventricle in the absence of angiographic evidence of obstructive coronary artery disease (CAD). A variety of stress-related triggers, including malignancies, have been reported in patients with TTC. However, to our knowledge, a recent diagnosis of a colon mass preceding the development of TTC has not been reported. We report on a female patient who was recently diagnosed with a colon mass by colonoscopy who was then scheduled to undergo robotic hemicolectomy, but was subsequently admitted to our hospital for intractable nausea and abdominal pain. While admitted, she developed transient ventricular tachycardia with elevated cardiac markers. The echocardiogram revealed markedly decreased ejection fraction and mid to distal apical akinesis with regional wall motion abnormalities. Coronary angiogram demonstrated no significant CAD, consistent with the diagnosis of TTC. The recently diagnosed colon mass was the most likely stress trigger in the development of TTC.